A new approach to cosmological structure formation with massive neutrinos - Fidler, Christian; Rampf, Cornelius (Journal of cosmology and astroparticle physics, 2019)
We show how Newtonian cosmological simulations can be employed to investigate the non-linear evolution of two particle species in a relativistic context. We discuss the application for massive neutrinos and other multi-species systems such as Cold Dark Matter (CDM) plus baryons or Warm Dark Matter (WDM) . We propose a method that allows us to perform simulations including massive neutrinos and general relativistic effects at almost the same computational cost as ordinary CDM only N-body simulations, employing tailor-made initial conditions and a dictionary for the interpretation of the simulation output.
Gesehen am 23.07.2019